2002
DOI: 10.1093/toxsci/68.2.331
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Progression of Asbestos-Induced Mesotheliomas in Heterozygous p53+/- Mice

Abstract: Asbestos fibers produce diffuse malignant mesotheliomas in chronic rodent inhalation assays or after direct intrapleural or intraperitoneal injection. In vitro models have provided evidence that asbestos fibers are genotoxic carcinogens that can directly or indirectly generate reactive oxygen- and nitrogen-derived species that cause DNA damage. Heterozygous p53+/- mice show an increased incidence and reduced latency of malignant mesotheliomas induced by weekly intraperitoneal injections of crocidolite asbestos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 28 publications
2
44
0
1
Order By: Relevance
“…When asbestos was applied intraperitoneally to this model, mesotheliomas were induced with short latency as well (Marsella et al,1997;Vaslet et al,2002). Here, although the genotoxic effect of MWCNT is unclear, our results suggested that intraperitoneal administration of MWCNT possesses carcinogenic potential in p53(+/−) mice presumably depending on its size/shape and persistency in the organism.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…When asbestos was applied intraperitoneally to this model, mesotheliomas were induced with short latency as well (Marsella et al,1997;Vaslet et al,2002). Here, although the genotoxic effect of MWCNT is unclear, our results suggested that intraperitoneal administration of MWCNT possesses carcinogenic potential in p53(+/−) mice presumably depending on its size/shape and persistency in the organism.…”
Section: Discussionmentioning
confidence: 58%
“…Deduced from those factors, we hypothesized that MWCNT might have carcinogenic potency similar to asbestos when administered to organisms via the same route of exposure. Here, we adopted a short-term bioassay, i.e., the p53 heterozygous mouse intraperitoneal exposure model reported to be sensitive to asbestos and develop mesotheliomas fast (Marsella et al, 1997;Vaslet et al, 2002). This mouse model has been reported to be sensitive not only to genotoxic carcinogens (Pritchard et al, 2003) but also to reactive oxygen species (ROS)-related carcinogenesis (Tazawa et al, 2007) and therefore fits with the postulated carcinogenesis mechanisms of asbestos and asbestos-like particles (Marsella et al, 1997;Vaslet et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This further emphasises the differences between radiation-induced apoptosis and that resulting from a carcinogen. Although tumour suppression by p53 is tissue type-dependent, a decrease in dosage of the p53 gene has been shown to promote carcinogen-induced tumorigenesis at many sites, 34,35 including skin, 36 bladder, 37 lung, 38 salivary gland 39 and oesophagus. 40 These studies have shown that p53 is important in controlling early events in oncogenesis in these tissues, but it has not been clear until now that this also applied to colon.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was isolated from primary murine malignant mesothelioma cell cultures, and exons 4 to 11 of the Tp53 gene were PCR amplified using Platinum Taq DNA Polymerase High Fidelity (Invitrogen, Carlsbad, CA), as previously described (14). The products were cloned into a pCRII-Topo vector (Invitrogen) and sequenced using Tp53 intron-specific forward and reverse primers.…”
Section: Methodsmentioning
confidence: 99%